2017
DOI: 10.1038/ncomms15293
|View full text |Cite
|
Sign up to set email alerts
|

Heterodimerization of Munc13 C2A domain with RIM regulates synaptic vesicle docking and priming

Abstract: The presynaptic active zone protein Munc13 is essential for neurotransmitter release, playing key roles in vesicle docking and priming. Mechanistically, it is thought that the C2A domain of Munc13 inhibits the priming function by homodimerization, and that RIM disrupts the autoinhibitory homodimerization forming monomeric priming-competent Munc13. However, it is unclear whether the C2A domain mediates other Munc13 functions in addition to this inactivation–activation switch. Here, we utilize mutations that mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
107
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(121 citation statements)
references
References 48 publications
(117 reference statements)
12
107
2
Order By: Relevance
“…(F)] and activates vesicle priming by disrupting the C 2 A domain homodimer . In addition, heterodimerization of αRIMs with the Munc13‐1 C 2 A domain plays an important role in docking‐priming, as a mutation that disrupts both homo and heterodimerization leads to a 50% decrease in vesicle priming and in the number of docked vesicles, similar to that observed upon deletion of the entire N‐terminal region . However, a mutation that disrupts only the heterodimer has a similar effect in docking but a much stronger effect on priming, suggesting that homodimerization may allow docking while hindering fusion.…”
Section: Munc13‐1 As a Master Regulator Of Neurotransmitter Releasementioning
confidence: 88%
See 2 more Smart Citations
“…(F)] and activates vesicle priming by disrupting the C 2 A domain homodimer . In addition, heterodimerization of αRIMs with the Munc13‐1 C 2 A domain plays an important role in docking‐priming, as a mutation that disrupts both homo and heterodimerization leads to a 50% decrease in vesicle priming and in the number of docked vesicles, similar to that observed upon deletion of the entire N‐terminal region . However, a mutation that disrupts only the heterodimer has a similar effect in docking but a much stronger effect on priming, suggesting that homodimerization may allow docking while hindering fusion.…”
Section: Munc13‐1 As a Master Regulator Of Neurotransmitter Releasementioning
confidence: 88%
“…The N‐terminal region of Munc13‐1 is also involved in diverse forms of regulation of release. Deletion of this region (residues 1–520) leads to a 50% decrease in evoked release, while deletion of only the C 2 A domain (residues 1–150) causes a much more dramatic impairment of release, and deletion of the linker region spanning residues 151–520 has mild effects on release . These results indicate that the linker region plays an inhibitory role and that the C 2 A domain is critical to relieve this inhibition.…”
Section: Munc13‐1 As a Master Regulator Of Neurotransmitter Releasementioning
confidence: 96%
See 1 more Smart Citation
“…In this study, we analyzed the functional importance of the C2A domain of UNC-13L, a Munc13-1 homolog in C. elegans, for SV priming and release probability. Prior studies in mouse and C. elegans have reported contradictory results regarding the role of the C2A domain in priming (Betz et al, 2001;Zhou et al, 2013a;Camacho et al, 2017). This motivated us to investigate the function of this domain, with a particular focus on its two bindings modes, in SV priming and postpriming Ca 2+ -triggered exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Betz et al first found that the C2A domain binds to the zinc finger (ZF) domain or RIM, an active zone protein that is required for SV priming (Betz et al, 2001). A double mutation in mouse RIM's ZF domain (K144/146E) disrupts C2A/RIM heterodimerization (Dulubova et al, 2005) and was subsequently shown to produce a large reduction in the readily releasable pool (RRP) of SVs following Camacho et al, 2017), indicating that C2A binding to RIM plays an important role in SV priming. Apart from forming a heterodimer with RIM, the C2A domain also forms a homodimer, thereby promoting formation of MUNC13-1 homodimers.…”
Section: Introductionmentioning
confidence: 99%